pH-regulated nuclear F-actin assembly during ferroptosis - Qiao, Menghao; Yan, Zhipeng; Huang, Jiewei; Fang, Yu; Xu, Kun; Cao, Lingbo; Mai, Haiying; Li, Na; Li, Yanmei; Guo, Yunmiao; Huang, Junqi (Frontiers in Cell and Developmental Biology, 2025)
IntroductionFerroptosis is an iron-dependent form of programmed cell death driven by lipid peroxidation and loss of membrane integrity, frequently modeled with small molecules such as RSL3 that inhibit Glutathione Peroxidase 4 (GPX4). Filamentous actin (F-actin) exists within the nucleus, modulating transcription, nuclear mechanics, and chromatin organization, yet its behavior during ferroptosis remain unexplored.MethodsHere, we show that nuclear F-actin assembles in HT-1080 cells undergoing RSL3-induced ferroptosis, visualized by phalloidin, SiR-actin, anti-Actin staining, and live 3D/time-lapse imaging of a nuclear actin chromobody (nAC-TagGFP2).ResultsMechanistically, nuclear G-actin increased during ferroptosis, and Importin-9 (IPO9) knockdown markedly reduced nuclear F-actin, indicating an import-dependent mechanism. Concurrently, cytoplasmic F-actin underwent substantial remodeling. Overexpression of a polymerization-defective cytoplasmic β-actin mutant (R62D) slightly delayed ferroptosis, whereas nuclear-targeted mutants had no effect, suggesting nuclear F-actin is a concomitant, not causative, feature. Notably, extracellular NaHCO3 or NaOH suppressed nuclear F-actin formation, while a pH-sensitive reporter revealed progressive intracellular acidification during ferroptosis, favoring nuclear F-actin assembly.DiscussionThese findings reveal nuclear F-actin assembly driven by cytoplasmic actin remodeling, nuclear import, and intracellular acidification, uncovering a previously unrecognized feature of ferroptotic cell death.